Pengaruh Kualitas Pelayanan dan Harga Terhadap Kualitas Produk dengan Kepuasan Pelanggan Sebagai Variabel Intervening pada Budiman - Rian Safitri; Chintya Ones Charli; Sri Meliana; Bhadra Ananda Detria (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study was to analyze the effect of service quality and price on product quality with customer satisfaction as an interevening variable with a sample of 50 in Budiman, Padang City, West Sumatra. This type of research is explanatory research. The method used for data collection uses questionnaire surveys given to respondents. Smart PLS analysis method.